Subarachnoid hemorrhage due to aneurysm rupture in a young woman with Alagille syndrome – A rare cause of sudden death. Issue 5 (September 2015) - Doberentz, E.; Kuchelmeister, K.; Madea, B.
Highlights The Alagille syndrome is a rare, autosomal dominant inherited disease which is mainly characterized by a reduction of the number of bile ducts leading to cholestasis. Several other organs may be effected. In the presented case a 25 year old woman with Alagille syndrome who had liver transplantation in the age of 7 and 8 years died suddenly and unexpectedly. Cause of death was a subarachnoidal hemorrhage due to rupture of an undiagnosed aneurysm of the basilary artery. Due to the high rate of vascular complications in patients with Alagille syndrome a vascular screening may be necessary.